The use of strip crown material in the restoration of permanent incisors after endodontic treatment (Эндодонтия Today, 2020)
The entire course of the conducted treatment of fractured crown incisors after endodontic treatment is described. Treatment results were confirmed by X-Ray.The treatment plan was divided into 4 parts:examination,endodontic treatment, therapeutic (the strip crown restoration) and observation (recall)